LANGUAGE EDUCATION IN THE MULTI-USER VIRTUAL ENVIRONMENT - MARESOVA, Hana (Trends in education, 2009)
The article refers to the possibilities of use the multi-user virtual environment (MUVE) applications in the language education. The differences between the early communication tools and MUVE is based especially on the simulation of real environment by 3D virtual graphics objects, 3D graphical representation of each user (avatar) or communication by virtual ``face to face'' in real time. The projects from foreign and Czech internet and MUVEs focused on the language education are analyzed.
Keywords: multi-user virtual environment; language education; e-learning; online education.